Seamless multimodality for passenger transportation in the Russian Federation - A. S. Stepanenko; A. S. Bolt; P. S. Bolt (Вестник университета, 2024)
The paper considers the formation of a seamless multimodal passenger transportation in order to develop transport infrastructure not only at the regional but also at the federal level. The positive aspects and disadvantages of a multimodal transport system are considered. The paper presents a review of the scientific literature on the above issues. The research methodology is based on proven approaches. Founded on the analysis of the tourist flow, it is proposed to build a system of seamless multimodal transportation in the territory of the Russian Federation (hereinafter referred to as RF). The relevance is due to the need to develop regional transport systems as well as consideration of this topic in the scientific literature, regulatory documents of the industry. Based on the Strategic direction in the field of digital transformation of the transport industry of the RF until 2030, the principles of multimodality are proposed to create a seamless system of multimodal passenger transportation. The development has been conducted for the transport system of the Altai Territory. Based on the data on tourist flows of the Federal State Statistics Service, the calculated route Moscow – Barnaul – Gorno-Altaysk is formed. The introduction of a digital platform for convenient search and booking of transportation is considered, the key points of working with requests are highlighted. The movement of financial and information flows and the algorithm of actions of the system participants are determined.